Bactericidal, anti-hemolytic, and anticancerous activities of phytofabricated silver nanoparticles of glycine max seeds - Kumar, K. B. Vijendra; Varadaraju, Kavitha Raj; Shivaramu, Prasanna D.; Kumar, C. M. Hemanth; Prakruthi, H. R.; Shekara, B. M. Chandra; Shreevatsa, Bhargav; Wani, Tanveer A.; Prakasha, K. C.; Kollur, Shiva Prasad; Shivamallu, Chandan (Frontiers in Chemistry, 2024)
Soyabean is a rich source of bioactive components with good nutritional support and is easily available. In the treatment of cancer, green synthesis of silver nanoparticles (AgNPs) from plantbased samples have gained attentions due to its potency and feasibility. In the present study, using soyabean extract (GM), silver nanoparticles are synthesized and analysed for its anticancer potency. The synthesized GM-AgNPs were characterised by UV-vis spectroscopy, Fourier transform-infrared (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive X-ray (EDX), techniques for further analysis. Antibacterial activity by disc method, anti-hemolysis activity in in-vitro method and followed by anticancer properties evaluation by cytotoxicity, cell migration, apoptosis, cell cycle. Our results were, that the synthesized GM-AgNPs were spiral shape with size range of 5-50nm. In antibacterial activity against Staphylococcus aureus and Klebsiella pneumoniae showed the maximum zone of inhibition at 250µg/ml in comparison with gentamicin. On exploring anti-hemolysis efficiency, at 200µg/ml GM-AgNPs showed no hemolysis in comparison with the extract which showed 40% of lysis. On analysis of GM-AgNPs against breast cancer cell line, displayed IC50 of 74.04µg/ml. Further at the IC50 concentration, cancer cell migration was reduced. The mechanism of action of GM-AgNPs confirmed the initiation of apoptosis and cell cycle arrest in sub G0/G1 (growth phase) phase by 48.19%. in gene expression and protein expression analysis BAX and BCl-2 was altered to that of normal physiology.